Pedagang etnis Minangkabau di pasar Tanah Abang Jakarta Pusat (1975 – 2023) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
Tanah Abang Market, the largest textile trade center in Indonesia and Southeast Asia, functions as a multicultural economic hub that attracts traders from various ethnic groups. This study focuses on Minangkabau traders—the dominant group in the market—to analyze their historical dynamics, business strategies, adaptation mechanisms, and the factors that limit their economic advancement. Using the historical method (heuristics, source criticism, interpretation, and historiography), data were collected from newspapers, scholarly literature, and interviews with active traders. The findings show that Minangkabau traders began participating in the market in the 1970s, driven by government support through the Small Investment Credit (KIK), Permanent Working Capital Credit (KMKP), and pro-indigenous entrepreneurship policies. Government-led modernization and expansion of Tanah Abang Market further accelerated their growth. Initially operating as street vendors due to limited capital, they gradually obtained permanent kiosks. However, despite their numerical dominance, their economic progress remained limited due to restricted access to capital, short-term profit orientation, and challenges in adapting to modern market dynamics. This study contributes to the understanding of ethnic socio-economic adaptation in urban commercial spaces and serves as a reference for future research on ethnic entrepreneurship and market transformation in Indonesias.
Keywords: Economic adaptation; indigenous entrepreneurship; historical study; Minangkabau traders; Tanah Abang Market